2.4‐GHz Power Amplifier with Power Detector Using Metamaterial‐Based Transformer‐Type On‐Chip Directional Coupler. Issue 3 (1st June 2013) - Dang, Trung‐Sinh; Tran, Anh‐Dung; Lee, Bomson; Yoon, Sang‐Woong
Abstract : This letter presents a power amplifier (PA) with an on‐chip power detector for 2.4‐GHz wireless local area network application. The power detector consists of a clamp circuit, a diode detector, and a coupled line directional coupler. A series inductor for an output matching network in the PA is combined with a through line of the coupler, which reduces the coupling level. Therefore, the coupler employs a metamaterial‐based transformer configuration to increase coupling. The amount of coupling is increased by 2.5 dB in the 1:1 symmetric transformer structure and by 4.5 dB from two metamaterial units along the coupled line.